Premature Failure and its Prevention in Flexural Beams Retroftted by GFRP Fibers - Eskenati, Amir Reza; Pour, Hamid Varasteh (Journal of the Institute of Engineering, 2016)
Nowadays, retroftting reinforced concrete with FRP fbers is regarded as a globally signifcant issue. In reinforced concrete beam, the shear failure mode is more dangerous than fexural failure mode. Because this thin and sudden mode occurs without any pre-warning, diagonal shear cracks are wider than fexural cracks and preventing their expansion is rather diffcult. In the present study, the concrete beams are retroftted with GFRP fbers through a common method. Then, the beams have four- point bending test until the premature failure occurs. This phenomenon is relatively prevented through retroftting along the shear. The failure of beams are examined here. Journal of the Institute of Engineering, 2015, 11(1): 12-19